HIV-induced Retinitis. (16th November 2020) - Wons, Juliana; Kempen, John; Garweg, Justus G.
ABSTRACT: Purpose: To provide an overview of the current knowledge on the Human Immunodeficiency Virus (HIV)-associated retinopathies. Methods: A PubMed search was performed, using the key terms "HIV Retinopathy OR Retinitis" and "HIV AND Retinitis" to find manuscripts published within the last ten years. Results: If left untreated, HIV infection causes a progressive immunodeficiency caused by depletion of CD4-positive T lymphocytes. Noninfectious HIV retinopathy, clinically manifested by cotton wool spots. Once the CD4 count drops below 200 c/μl, immunodeficiency creates a vulnerability for systemic opportunistic infections. Within the posterior segment of the eye, cytomegalovirus (CMV) retinitis has to be distinguished from infections with other members of the herpes virus family, as well as from toxoplasmosis, tuberculosis, and syphilis. Upon restoration of the immune system, immune recovery uveitis may manifest in one third of CMV affected eyes. Conclusion: Targeted antiviral treatment and secondary recurrence prophylaxis prevent vision loss of the retina prior to immune recovery.